2021
DOI: 10.1002/bies.202100186
|View full text |Cite
|
Sign up to set email alerts
|

Processed pseudogenes: A substrate for evolutionary innovation

Abstract: Processed pseudogenes may serve as a genetic reservoir for evolutionary innovation. Here, we argue that through the activity of long interspersed element-1 retrotransposons, processed pseudogenes disperse coding and noncoding sequences rich with regulatory potential throughout the human genome. While these sequences may appear to be non-functional, a lack of contemporary function does not prohibit future development of biological activity. Here, we discuss the dynamic evolution of certain processed pseudogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 102 publications
0
9
0
Order By: Relevance
“…3 a, b). Although most pseudogenes are thought to be nonfunctional, a few transcribed pseudogenes have been reported to obtain the defined functions through rapid evolution 44 . Our results reveal that most RPLP2 processed pseudogenes in P. glacialis harbor faster evolutionary rate (Ka/Ks) than that of complete RPLP2 genes among eight butterflies (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3 a, b). Although most pseudogenes are thought to be nonfunctional, a few transcribed pseudogenes have been reported to obtain the defined functions through rapid evolution 44 . Our results reveal that most RPLP2 processed pseudogenes in P. glacialis harbor faster evolutionary rate (Ka/Ks) than that of complete RPLP2 genes among eight butterflies (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…S1). This phenomenon results from the fact that each of these genes belongs to a large gene family whose members share some conserved domains with each other, and these functional paralogs (family members) underwent further duplication likely through retrotransposition that gave rise to hundreds of thousands of truncated pseudogenes (Troskie, et al 2021). Meanwhile, high duplication levels of a few genes in certain species (e.g.…”
Section: Longevity-associated Genes Underwent a Higher Rate Of Expans...mentioning
confidence: 99%
“…Typically, pseudogenes derived from retrotransposition lack the upstream of the promoters of their parental genes. To obtain transcriptional activity, pseudogenes must be located downstream of a pre-existing promoter in close proximity, or a novel promoter must evolve (Troskie, et al 2021). By analysing the loci of PIK3R1 duplications in the genomes of H. glaber and M. myotis, we noticed that most of them are located either in introns or intergenic regions adjacent to protein-coding genes.…”
Section: Pik3r1 May Have Experienced Convergent Duplications In the L...mentioning
confidence: 99%
“…A 2021 review in Nature found that over 130,000 discrete genetic elements 'previously called junk DNA' have been already reported in the literature to have biological functions -and showed that functions for non-coding DNA are being discovered at a rapid pace (Gates et al 2021). Even pseudogenes, frequently cited as a form of genetic junk that demonstrates common ancestry, are no longer considered to necessarily be genetic 'junk' (Cheetham, Faulkner & Dinger 2020;Kovalenko & Patrushev 2018;Pink et al 2011;Poliseno 2012;Poliseno et al 2010;Troskie, Faulkner & Cheetham 2021). The assumption that non-coding DNA that we share with apes is merely functionless 'junk' reflecting our common ancestry is no longer sustainable.…”
Section: Human-chimp Genetic Similaritymentioning
confidence: 99%